Descriptive study of implementation of health protocols for people with HIV-AIDS during the pandemic of covid-19 - kholizah, Siti; Afritayeni, Afritayeni; Yanti, Penti Dora; Rustam, Musfardi; Rustam, Martha Hasanah (CORE JOURNAL, 2022)
HIV (Human Immunodeficiency Virus) is a virus that attacks the immune system so that the body is susceptible to various diseases. While AIDS (Acquired Immune Deficiency Syndrome) is a collection of symptoms or diseases caused by decreased immunity due to infection by the HIV virus. People living with HIV/AIDS (PLWHA) are at high risk of being exposed to the COVID-19 virus, which is also closely related to the immune system. The purpose of this study was to determine the behavior of PLWHA in carrying out health protocols during the Covid-19 period at the Lima Puluh Health Center in Pekanbaru City in 2021. The type of research was quantitative with a descriptive design. The population in this study were all PLWHA who took drugs and were active at the Limapuluh Pekanbaru Health Center for the July-August 2020 period, totaling 151 people living with HIV. Sampling using the SLOVIN formula with a total of 60 respondents. Univariate data analysis. The results of the study found negative behavior in 34 people (56.7%). It is hoped that respondents will be given health education to comply with health protocols by implementing clean hand washing, wearing masks and keeping a distance